Investment in irrigation for global food security - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
What will it take to achieve a level of irrigation investment sufficient to support sustainable agriculture for improved food security and nutrition? Climate change and all the resulting uncertainties are sparking new interest in raising investments in irrigation to enable more stable food production. In order for these investments to pay off, they need to be targeted and ideally should be accompanied by the following: 1. Support for smallholder irrigation systems whenever feasible. 2. Improvements in water-use efficiency 3. Economic incentives to conserve water resources 4. Linkages with other sectors. 5. Linkages between irrigation and nutrition